2007
DOI: 10.1080/10284150701565540
|View full text |Cite
|
Sign up to set email alerts
|

Classical conditioning of the rabbit's nictitating membrane response is a function of the duration of dietary cholesterol

Abstract: Modifying dietary cholesterol may improve learning and memory but very high cholesterol can cause pathophysiology and death. Rabbits fed 2% cholesterol for 8, 10 or 12 weeks with 0.12 ppm copper added to distilled water and rabbits fed a normal diet without copper added to distilled water (0 weeks) were given a difficult trace classical conditioning task and an easy delay conditioning task pairing tone with corneal air puff. The majority of cholesterol-fed rabbits survived the deleterious effects of the diet b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 69 publications
5
22
0
Order By: Relevance
“…This is a finding we have seen in many of our subsequent experiments [4850]. The facilitated conditioning was indexed by higher levels of responding to the CS [32, 48] and heightened responsivity to the US measured after conditioning, and known as a conditioning-specific reflex modification [32, 4850]. When the levels of beta amyloid accumulation in our cholesterol-fed rabbits were examined by the Sparks laboratory, the immunoreactivity was relatively light although significantly higher than in the rabbits fed normal chow.…”
Section: The Effects Of Cholesterol On Learningsupporting
confidence: 76%
See 1 more Smart Citation
“…This is a finding we have seen in many of our subsequent experiments [4850]. The facilitated conditioning was indexed by higher levels of responding to the CS [32, 48] and heightened responsivity to the US measured after conditioning, and known as a conditioning-specific reflex modification [32, 4850]. When the levels of beta amyloid accumulation in our cholesterol-fed rabbits were examined by the Sparks laboratory, the immunoreactivity was relatively light although significantly higher than in the rabbits fed normal chow.…”
Section: The Effects Of Cholesterol On Learningsupporting
confidence: 76%
“…This is a finding we have seen in many of our subsequent experiments [4850]. The facilitated conditioning was indexed by higher levels of responding to the CS [32, 48] and heightened responsivity to the US measured after conditioning, and known as a conditioning-specific reflex modification [32, 4850].…”
Section: The Effects Of Cholesterol On Learningmentioning
confidence: 54%
“…In summary, this is the first report to show dietary cholesterol concentrations affect both the electrophysiological properties and dendrite spine morphology in rabbit hippocampal CA1 pyramidal neurons, which can account for dietary cholesterol facilitated learning of a new task and degraded memory recall of acquired learning task in our previous experiments (Darwish et al, 2010; Schreurs et al, 2007a; Schreurs et al, 2007c; Schreurs et al, 2012; Schreurs et al, 2013). …”
Section: Discussionsupporting
confidence: 49%
“…Some of these studies show dietary cholesterol improved learning and memory (Dufour et al, 2006; Schreurs et al, 2003) while others show a cognitive deficit (Darwish et al, 2010; Sparks and Schreurs, 2003) that is accompanied by neuropathological changes especially when copper was added to the drinking water (Sparks and Schreurs, 2003; Woodruff-Pak et al, 2007). Further studies confirmed that the effects of dietary cholesterol on learning and memory may be dependent on the amount and duration of dietary cholesterol (Schreurs et al, 2007a; Schreurs et al, 2012), animal age and species (Dufour et al, 2006; Granholm et al, 2008). Therefore, there is evidence for an effect of dietary cholesterol on behavior although the consequences may be either beneficial or detrimental and the mechanisms are still unclear.…”
Section: Introductionmentioning
confidence: 70%
“…Prompted by Sparks’ original observation that cholesterol-fed rabbits developed elevated levels of neuronal beta amyloid (Sparks et al ., 1994), we were surprised to find that rabbits fed cholesterol for eight weeks showed improved trace classical conditioning and reflex facilitation of the NMR (Schreurs et al ., 2003) and that these facilitating effects of cholesterol were a function of the concentration (Schreurs et al ., 2007b) and duration of the cholesterol diet (Schreurs et al ., 2007a). These facilitating effects were generalized beyond NMR conditioning because an eight-week, 2% cholesterol diet also facilitated rabbit heart rate conditioning – an index of conditioned fear (Schreurs et al ., 2007c).…”
Section: Cholesterolmentioning
confidence: 99%